2009
DOI: 10.1055/s-0029-1211383
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine cell to cell interactions determine the effects of pituitary adenylate cyclase activating polypeptide (PACAP) on in vitro prolactin release from rat pituitary cells

Abstract: In static cultures of dispersed rat pituitary cells and in the reverse hemolytic plaque assay PACAP inhibits prolactin (Prl) secretion, while in vivo application of PACAP stimulates Prl release in rats. To elucidate the mechanism of this contradictory action, we compared the in vitro effects of PACAP on Prl secretion in cultures of dispersed or reaggregated cells and in pituitary fragments. While in monolayer cultures Prl release was inhibited by PACAP, in cultures of aggregated cells and in pituitary fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In contrast, other studies have shown that PACAP can either slightly increase (Arbogast and Voogt, 1994) or inhibit ) PRL release from rat pituitary cells. To elucidate the origin of these apparent discrepancies, the effects of PACAP on PRL secretion have been compared in cultures of dispersed or aggregated cells and in pituitary fragments (Benter et al, 1995). In monolayer cultures, PRL release was inhibited by PACAP, whereas in cultures of aggregated cells and in pituitary fragments, PRL output was stimulated (Benter et al, 1995).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, other studies have shown that PACAP can either slightly increase (Arbogast and Voogt, 1994) or inhibit ) PRL release from rat pituitary cells. To elucidate the origin of these apparent discrepancies, the effects of PACAP on PRL secretion have been compared in cultures of dispersed or aggregated cells and in pituitary fragments (Benter et al, 1995). In monolayer cultures, PRL release was inhibited by PACAP, whereas in cultures of aggregated cells and in pituitary fragments, PRL output was stimulated (Benter et al, 1995).…”
mentioning
confidence: 99%
“…To elucidate the origin of these apparent discrepancies, the effects of PACAP on PRL secretion have been compared in cultures of dispersed or aggregated cells and in pituitary fragments (Benter et al, 1995). In monolayer cultures, PRL release was inhibited by PACAP, whereas in cultures of aggregated cells and in pituitary fragments, PRL output was stimulated (Benter et al, 1995). These data suggest that cell-to-cell communication plays a crucial role in determining the type of action of PACAP on PRL secretion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in ovine and bovine pituitary cells, PACAP had no effect on prolactin release [70,71]. Conversely, other studies demonstrated the stimulating effect of PACAP on prolactin release [72,73]. In prolactin-producing model GH3 cells that originate from rat pituitary somatolactotrophs, PACAP increases the synthesis and secretion of prolactin with a concomitant activation of ERK and cAMP/PKA pathways [74].…”
Section: Prolactin Synthesis and Secretion From Pituitary Lactotrophsmentioning
confidence: 99%
“…PACAP effects on PRL release are controversial and depend on the test system used (207211). Whereas PACAP inhibits PRL release in monolayer cell cultures, it stimulates release in aggregate cell cultures and in vivo (207, 212). In studies where a stimulation of PRL release by PACAP was found in monolayer culture, the effect is probably on PRL gene expression and translation as it was only found after several hours of treatment (213).…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 99%